2015
DOI: 10.1016/j.proeng.2015.01.203
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Tablet Strength from the Wet Granulation Conditions via the Unified Compaction Curve

Abstract: Tablets make up approximately one third of all drug dosage forms which makes tablet manufacture a common process in the pharmaceutical industry. The unified compaction curve [1] is a model developed initially to look at the impact of the roller compaction conditions on the tablet strength. The tensile strength of the tablets made from formulations containing at least 50% microcrystalline cellulose produced at roller compaction pressures were measured and the profiles were collapsed into a single master "unifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Accordingly, the higher the concentration of the binder solution the harder will be the granules and the higher will be the compression force that needed for fragmentation and/or deformation to form compact formation. This finding is in agreement with that published by Nguyen et al [20]. .…”
Section: Effects On Tablets' Hardnesssupporting
confidence: 94%
See 1 more Smart Citation
“…Accordingly, the higher the concentration of the binder solution the harder will be the granules and the higher will be the compression force that needed for fragmentation and/or deformation to form compact formation. This finding is in agreement with that published by Nguyen et al [20]. .…”
Section: Effects On Tablets' Hardnesssupporting
confidence: 94%
“…It could be true that crushing strength of the granules tends to increase as a consequence of increasing the concentration of the binder solution; however, this might not correlates with the tablets strength [19,20]. The compression process results in a decrease in powder volume; owing to elastic and/or plastic deformation and the degree of particle attrition behaviors of the particle-particle bonds in the powder mass [21].…”
Section: Effects On Tablets' Hardnessmentioning
confidence: 99%
“…The graph of absorbance vs. concentration for sitagliptin phosphate monohydrate was found to be linear in the concentration range of 0-10 µg/mL at 267 nm. The R 2 of the calibration curve was found to be 0.999, which concludes that it follows the Beers Lambert's law within this concentration range 13 . Infrared Spectroscopy: The FTIR spectrum of the API shown in Fig.…”
Section: Fig 2: Uv Spectrum Of Sitagliptin Phosphate Monohydratementioning
confidence: 57%
“…Wavelength of maximum absorbance (λ max ) of sitagliptin phosphate monohydrate was found to be 267 nm in distilled water 13 .…”
Section: Uv-spectroscopy (Determination Of λ Max )mentioning
confidence: 99%
“…The lowering of tensile strength of tablets formulated with C-PE as diluents may be associated with the inability of the diluents to exert their effect as directly compressible excipients in tablets formulated by wet granulation. Formulation studies have shown that directly compressible excipients tend to lose their compressibility when incorporated in tablet formulations by wet granulation (Nguyen et al, 2015). Tablet friability parameter was evaluated to measure the weakness of the tablet.…”
Section: Resultsmentioning
confidence: 99%